Simulation of microstructure evolution of AZ31 magnesium alloy during indenten-flatten compound deformation technology based on cellular automata. (2017) - Wang, Zhongtang; Wang, Lingyi; Gao, Shengdong
Indentation-flattening compound deformation technology (IFCDT) is defined, and the characteristics of IFCDT are discussed. Microstructure evolution of dynamic recrystallisation of AZ31 magnesium alloy during IFCDT was simulated by cellular automaton method (CA). Dynamic recrystallisation of AZ31 magnesium alloy deformed by IFCDT is analysed. Grain shape, distribution, orientation and size is analysed. When holding time is constant, the grain size increases significantly with increasing of deformation temperature. When deformation temperature is constant, the grain size increases slightly with increase of holding time. With the increase of reduction, the grain size decreases obviously. When the reduction is 2 mm, dynamic recrystallisation is not appearing. Comparing simulation results with those of experiment, the maximum relative error is 15.4%. It is proved that cellular automaton method may be used to predict the microstructure evolution of AZ31 magnesium alloy during IFCDT.